Single-shot measurement of the photonic band structure in a fiber-based Floquet-Bloch lattice - Corentin Lechevalier (Nature Portfolio, 2021)
Floquet-Bloch lattices are systems that are relatively difficult to implement in solid-state physics. Here, using a photonic lattice as an alternative, the authors experimentally observe Floquet-Bloch bands using a single-shot method which allows them to fully characterise the lattice eigenmode structure.